Mechanical, environmental, and cost evaluation of concrete using recycled polypropylene - Ade Okvianti Irlan; Herman Parung; M.W. Tjaronge; Muhammad Akbar Caronge (Case Studies in Chemical and Environmental Engineering)
This study investigates the mechanical, environmental and cost of concrete incorporating recycled polypropylene (PP) granules as partial fine aggregate replacement at 0 %, 10 %, 20 %, and 30 %, with water-to-cement (W/C) ratios of 0.45 and 0.55. The addition of PP granules reduced workability and density due to their hydrophobic and lightweight nature, leading to compressive strength reductions of up to 48 % at 30 % PP content. The optimal substitution level was identified at 10 %, achieving a balance between mechanical performance and environmental benefits. A strong exponential correlation between ultrasonic pulse velocity (UPV) and compressive strength was established (f'c = 0.045e0.0016v, R2 = 0.793), enabling reliable non-destructive strength prediction. Life cycle assessment (LCA) revealed that incorporating PP granules increased the global warming potential (GWP) by approximately 2–6 % at a 0.45 W/C ratio and 3–8 % at 0.55, primarily due to the energy-intensive recycling process. Additionally, the embodied energy (EE) increased by 5–15 % and 7–21 % at 0.45 and 0.55 W/C ratios, respectively. Although PP integration contributes to reducing natural aggregate consumption, its environmental benefits are constrained by higher embodied energy and costs, indicating its application is best limited to non-structural concrete where sustainability trade-offs can be justified.